Management and Treatment of Patients With Major Depressive Disorder and Chronic Diseases: A Multidisciplinary Approach - Almeida, Susana Sousa; Zizzi, Francesca Benedetta; Cattaneo, Agnese; Comandini, Alessandro; Di Dato, Giorgio; Lubrano, Ennio; Pellicano, Clelia; Spallone, Vincenza; Tongiani, Serena; Torta, Riccardo (Frontiers in Psychology, 2020)
In patients with physical chronic diseases, the prevalence of major depressive disorder (MDD) is approximately two- to three-fold higher that than in the general population, and it can reach up to 20-40%. The comorbidity of MDD with chronic medical diseases is associated with poorer quality of life, increased medical symptom burden, poor adherence to self-care regimens, increased risk of functional impairment, morbidity and mortality, and also higher medical costs. Despite this evidence, in routine practice, psychological issues and concerns are frequently inadequately managed. This consensus document proposes that a proper diagnosis, a multidisciplinary approach and a personalized treatment plan would allow patients with MDD and chronic comorbidities to be more compliant, to improve the outcomes, to reduce possible relapses in the long term and to prevent or better manage complications and adverse events. This proposal might be useful for any health professionals who deal with patients with chronic diseases, as it can help to pay more attention to the emotional impact of these conditions, in particular in terms of depressive symptoms.